Informal Aspects and Civil Procedure - Abdrasulov, Ermek B.; Onlanbekova, Galiya M.; Abdrasulova, Aizhan E. (The journal of contemporary issues in business and government, 2021)
Issues of relationship and interconnection of informal institutions and law as a set of rules of conduct established or sanctioned by the state in modern conditions of the civil society development acquire special relevance. Analyzing informal institutions, researchers often speak about the development of informal justice, informal justice and informal procedures in society as opposed to official, state justice, and “formal” procedures. As a rule, in general, we talk about alternative methods of resolving disputes. In this article, we tried to reveal the nature of the concept of “informal aspects” as a special phenomenon in its relationship with law in general and civil law in particular. Parallel to official justice non-state methods of dispute resolution are directly related to the freedom of choice by the parties not only of the norms of substantive law but also of the norms of other social regulators that do not contradict the rules of human life. In our study we analyze problems of informal methods practicing in formal justice on the example of negative judicial practice in Kazakhstan. The use of informal approaches and methods is often a sign of fair and lawful decision-making in state courts. This approach can exclude cases, when court decisions are obtained in the correct form, but in fact are anti-human.